Access to dihydropyridinones and spirooxindoles: application of N-heterocyclic carbene-catalyzed [3+3] annulation of enals and oxindole-derived enals with 2-aminoacrylates. Issue 44 (17th May 2017) - Zhao, Liang-Liang; Li, Xing-Shuo; Cao, Li-Li; Zhang, Rui; Shi, Xiao-Qian; Qi, Jing
Abstract : A strategy for the NHC-catalyzed synthesis of dihydropyridinones and spirooxindoles has been developed via [3+3] annulation reactions of enals or isatin-derived enals with 2-aminoacrylates under oxidative conditions. Abstract : A strategy for the NHC-catalyzed synthesis of dihydropyridinones and spirooxindoles has been developed via [3+3] annulation reactions of enals or isatin-derived enals with 2-aminoacrylates under oxidative conditions. In this efficient strategy, the 2-aminoacrylates served as nucleophiles. Modifying the standard base switched the carbon–carbon double bond formation from 5, 6-positions to 3, 4-positions to generate 5, 6-dihydropyridinones and 3, 4-dihydropyridinones, respectively. Meanwhile, a diverse set of spirooxindole derivatives were also synthesized in good to excellent yields.